NURSES KNOWLEDGE, ATTITUDE AND PRACTICE REGARDING INFLUENZA VACCINATION - JAZ, I; SADDIQUE, H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Influenza is a major public health concern, with vaccination being the most effective strategy for its prevention. Nurses play a vital role in promoting vaccination, yet barriers such as knowledge gaps and institutional challenges can hinder their adherence to vaccination practices. Objective: To assess the knowledge, attitudes, and practices of nurses regarding influenza vaccination in a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted with 113 nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with descriptive statistics summarizing key findings. Results: The majority of participants demonstrated limited knowledge, with only 47.8% correctly identifying the types of influenza viruses. Despite a generally positive attitude, with 44.2% agreeing to seek medical attention for influenza-like symptoms, vaccination practices were suboptimal. Only 18.6% of nurses frequently received the influenza vaccine, and 35.4% rarely encouraged their families to vaccinate. Conclusion: The findings underscore the need for targeted educational interventions and institutional policies to improve knowledge and vaccination practices among nurses. Enhancing these competencies is critical for reducing influenza transmission and improving public health outcomes.